PEMBUATAN RANGKAIAN KONTROL OTOMATIS UNTUK OVEN PENGERING BAHAN BAKU JAMU HERBAL DI CV. AMIR HERBAL - Deni Andriyansyah; Haikal Haikal; Arif Hidayat Purwono; Emanuel Budi Raharjo; Moch. Chamim (Abdi Masya, 2026)
CV. Amir Herbal is an SMEs engaged in the production of herbal medicine, with one of its important processes being the drying of raw materials in an oven. The problem partners face is the oven temperature control system, which is still manual, leading to temperature fluctuations, inconsistent product quality, and a high reliance on the operator. This community service activity aims to implement a temperature control-based oven automation system to improve temperature stability and the quality of drying results. The implementation method includes the observation stage, system design, equipment manufacturing and installation, implementation, and partner training. The system developed uses a PID controller REX-C100 integrated with a temperature sensor, solenoid valve, and an automatic gas-fueled ignition system. The implementation results show that the system maintains a more stable oven temperature relative to the setpoint value compared to the manual method. In addition, work efficiency increases due to reduced operator supervision requirements. The quality of the resulting herbal products is also more even and consistent. Thus, the implementation of this oven automation system has a positive impact on increasing productivity and production quality at CV. Amir Herbal has the potential to be further developed through the integration of digital-based monitoring technology